A Tree Unification Approach to Constructing Generic Processes - ZHANG, Linda L. (Institutional Knowledge at Singapore Management University, 2009)
In dealing with product diversity, manufacturing companies strive to maintain stable production by eliminating variations in production processes. In this respect, planning process families in relation to product families to achieve production stability is a promising approach. In this paper, the generic processes underlying process families and their construction is studied. Such generic processes entail well-structured mechanisms that can help companies develop similar processes to fulfill a diversity of customized products. In view of the fact that a production process is commonly represented by a tree, in particular, a binary tree, an approach based on tree unification to construct generic processes from large volumes of existing production data is proposed. This approach is tested using an industrial example involving electronic products, and the derived generic processes have been verified by the users.